Combined Computational and Experimental Study the Effect of Doped Magnesium into Betanine-sensitized TiO2 Photoanode for Dye-Sensitized Solar Cells Application - Yuly Kusumawati; Nanik Ismi Oktavianti; Linda Wati Oktavia; Nurul Widiastuti; Lukman Atmaja; Nur Izzati Abu Bakar; Nur Hadi (Universitas Gadjah Mada, 2019)
A preliminary study of the effect of magnesium-doped into betanine-sensitized TiO2 thin layers has been carried out computationally and experimentally. The computational calculation was performed to observe the effect of magnesium on the interaction molecular of betanine onto TiO2 surface, using Ti12O28H8 model cluster. It was found out that the distance of the oxygen on the anchoring site betanine with the Ti in TiO2/Mg cluster is shortercompare to that one in TiO2 cluster. This result confirms the bond between betanine and TiO2 is stronger in the case of Mg2+ incorporation. The Natural Population Calculation also confirms that the electron transport from betanine to the TiO2 is more facilitated after Mg2+ incorporation. These results are also supported by the HOMO-LUMO profile of TiO2-betanine and TiO2/Mg. The XRD and SEM measurement confirm those are no effect on the TiO2 structure and morphology with the incorporation of Mg2+. The thin-film UV-Vis measurement confirms there is a bandgap sift after the incorporation of Mg.